Pengaruh Metode Latihan Plyometric Vertical, Horizontal dan Kekuatan Otot Perut Terhadap Peningkatan Lompat Jauh di Kabupaten Kendal (Indonesian Journal for Physical Education and Sport, 2023)
The coaching is carried out routinely and structured, with the methods applied by the coach, the results of initial observations show that the jumps of PASI athletes in Kendal Regency, 8 athletes have 4 meters jumps and 11 athletes have less than 4 meters jumps. Therefore, programmed training is needed to improve the jumping ability of PASI athletes in Kendal Regency. The purpose of this study was to determine the effect of vertical, horizontal plyometric training methods and abdominal muscle strength on increasing the long jump in Kendal Regency. The sample in this study were 20 athletes from PASI Kendal Regency. The sampling technique used was total sampling technique while the data analysis technique used was statistical analysis technique using SPSS data statistical analysis assistance. The result of increasing the plyometric training method is 5.63% lower than the result of increasing the abdominal muscle strengthening exercise of 11.52%. The coaching is carried out routinely and structured, with the methods applied by the coach, the results of initial observations show that the jumps of PASI athletes in Kendal Regency, 8 athletes have 4 meters jumps and 11 athletes have less than 4 meters jumps. Therefore, programmed training is needed to improve the jumping ability of PASI athletes in Kendal Regency. The purpose of this study was to determine the effect of vertical, horizontal plyometric training methods and abdominal muscle strength on increasing the long jump in Kendal Regency. The sample in this study were 20 athletes from PASI Kendal Regency. The sampling technique used was total sampling technique while the data analysis technique used was statistical analysis technique using SPSS data statistical analysis assistance. The result of increasing the plyometric training method is 5.63% lower than the result of increasing the abdominal muscle strengthening exercise of 11.52%.